1990
DOI: 10.1002/hep.1840120103
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pressor response to vasopressin in patients with cirrhosis: Evidence for impaired buffering mechanisms

Abstract: In patients with cirrhosis, vasopressin infusion induces sustained vasoconstriction and elevation of arterial pressure. The vasopressor effect could be caused by impairment of mechanisms normally aimed at buffering increases in arterial pressure (reflex bradycardia and decreases in arteriolar resistance). We studied the acute effects of continuous vasopressin infusion (0.4 IU/min) on systemic hemodynamics in seven patients with cirrhosis and in six patients without cirrhosis (controls). Vasopressin effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The former has also been reported in dogs with baroreceptor denervation (99). Moreover, cirrhotic patients show an abnormally prolonged blood pressure response to vasopressin, and this has been ascribed to abnormal autonomic cardiovascular regulation (100). Vasopressin administration in septic shock does not produce the degree of bradycardia seen in normal individuals (40), suggesting impairment of normal baroreflexes.…”
Section: Autonomic Nervous System Dysfunctionmentioning
confidence: 91%
“…The former has also been reported in dogs with baroreceptor denervation (99). Moreover, cirrhotic patients show an abnormally prolonged blood pressure response to vasopressin, and this has been ascribed to abnormal autonomic cardiovascular regulation (100). Vasopressin administration in septic shock does not produce the degree of bradycardia seen in normal individuals (40), suggesting impairment of normal baroreflexes.…”
Section: Autonomic Nervous System Dysfunctionmentioning
confidence: 91%
“…Over the last 2 decades, there is accumulating evidence to suggest that the presence of cirrhosis per se is associated with significant cardiovascular abnormalities, irrespective of the cause of cirrhosis. These include resting increased cardiac output; decreased systemic vascular resistance [1]; reduced myocardial contractility or systolic incompetence, especially under conditions of stress, whether physiological [5], physical [6,7], or pharmacological [8]; increased thickness of the left ventricle [9][10][11], associated with diastolic dysfunction; and electrophysiological abnormalities [12][13][14]. This constellation of abnormalities has been termed cirrhotic cardiomyopathy [15].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on defects in the SNS, but several papers have emphasized the importance of vagal impairment for sodium and fluid retention [68,70]. Blood pressure responses to orthostasis are impaired, probably because of a blunted baroreflex function [71,72] and the cardiovascular responses to pharmacological stimulations with angiotensin II, noradrenaline and vasopressin are abnormal [73,74]. Captopril may, to some extent, correct vagal dysfunction in cirrhosis [68] and neuromodulation by the RAAS is also supported by data from Laffi et al, who recently reported that canrenone, an aldosterone antagonist, normalized cardiac responses to postural changes in compensated cirrhotic patients [72].…”
Section: Correction Of Circulatory Dysfunctionmentioning
confidence: 99%